2020
DOI: 10.3390/inorganics8010004
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic [Cu(P^P)(N^N)][PF6] Compounds with Isomeric Dibromo-1,10-Phenanthroline Ligands

Abstract: A series of [Cu(P^P)(N^N)][PF6] compounds are reported in which N^N is 2,9-dibromo-1,10-phenanthroline (2,9-Br2phen), 3,8-dibromo-1,10-phenanthroline (3,8-Br2phen) or 4,7-dibromo-1,10-phenanthroline (4,7-Br2phen) and P^P is bis(2-(diphenylphosphano)phenyl)ether (POP) or 4,5-bis(diphenylphosphano)-9,9-dimethylxanthene (xantphos). The compounds were characterized by solution multinuclear NMR spectroscopy, mass spectrometry and a single-crystal X-ray analysis. Each compound underwent a partially reversible or irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The photophysical properties of the complexes containing 2,9-phen are enhanced with respect to analogues containing 3,8-or 4,7-dibromo-1,10phenanthrolines. 111 More detailed investigations of these compounds have not been carried out. This journal is © The Royal Society of Chemistry 20xx…”
Section: Complex Cationmentioning
confidence: 99%
“…The photophysical properties of the complexes containing 2,9-phen are enhanced with respect to analogues containing 3,8-or 4,7-dibromo-1,10phenanthrolines. 111 More detailed investigations of these compounds have not been carried out. This journal is © The Royal Society of Chemistry 20xx…”
Section: Complex Cationmentioning
confidence: 99%
“…[ 12 ] The [Cu(xantphos)(3,8‐Br 2 phen)][PF 6 ] compound exhibited yellow emission with photoluminescence quantum yield of up to 21 % for it with an excited state lifetime τ 1/2 = 8.4 μs. [ 13 ] Therefore, the photocatalytic activity of [Cu(PˆP)(NˆN)][PF 6 ] compound should be improved by modifying the 3,8‐sites of phenanthroline. In view of this, whether this regularity can be confirmed in 3,8‐sites of phenanthroline is of interest to us.…”
Section: Introductionmentioning
confidence: 99%
“…The data in Table 2 are not clear-cut. However, considering the differences of E 1/2 ox of the [Cu(P^P)((MeO) 2 phen)] + and [Cu(P^P)((MeS) 2 phen)] + complexes, as well as the data previously reported on [Cu(P^P)(Br 2 phen)] + , 34 it can be concluded that the electron-donating or withdrawing effects of a specific substituent has a significant influence on the Cu + /Cu 2+ oxidation potentials.…”
Section: Electrochemical Propertiesmentioning
confidence: 86%
“…2,9-Br 2 phen was prepared following a literature route 33 and the NMR spectroscopic data matched those reported. 33,34 All other chemicals were purchased from Sigma Aldrich. Microwave reactions were carried out in a Biotage Initiator+ microwave reactor.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%